Avaliação experimental do processo estático de formação de reboco particulado em filtro prensa API - Fritoli, Giovani de Souza (2018)
Lost circulation is a problem detected in oil drilling operations, being characterized by the invasion of the drilling fluid in permeable formations. This problem, despite the additional costs it generates, may damage productive formations and, when uncorrected, reduce the well pressure, inducing kick occurrence. One of the corrective measures is to add lost circulation materials (LCM) to the drilling fluid with the objective of building a filter cake at the porous surface and therefore reduce the volume loss. In this work, particulate deposition on porous formations is experimentally analyzed to study the filter cake formation in oil drilling operations. The goal is to evaluate the influence of polymer additive (type and concentration), LCM’s (granulometry and concentration) e porous filter at filter cake formation. The experiments are conducted at an API filter press at pressures of 100 psi. Three polymers are utilized: xanthan gum (GX), carbopol (CBP) and carboxymethylcellulose (CMC) at concentrations of 1 and 2 lb/bbl to formulate non newtonian fluids and four particulate materials to constitute the filter cake (LCM’s), being two granulometries (2-44 e 44-106 μm) of calcium carbonate (CaCO3), one of glass spheres (180-300 μm) and one of plastic particles (250-420 μm). The polymer/particulate mixture is applied over three filter elements. An experimental procedure for the correct operation of the apparatus is developed and consists in pressurizing a mixture sample against a filter paper and measure the collected volume at the end (filtrate), filter cake thickness and mass wet and after drying The filtrate flow curve is obtained and compared to the reference formulations. Filtrate volume reduction is favored by the increase in polymer concentration, CMC being the most effective polymer at lost circulation mitigation, and LCM concentration and by the use of the smaller calcium carbonate. Filtrates present non newtonian behavior, however filtrate viscosity is lower than the reference fluids. This difference is detected more significantly for calcium carbonate as LCM.